2014
DOI: 10.1179/2050854914y.0000000023
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Hormonal Contraceptives on Glycemic Regulation

Abstract: A number of side effects have been linked to the use of hormonal contraceptives, among others, alterations in glucose levels. Hence, the objective of this mini-review is to show the main effects of hormonal contraceptive intake on glycemic regulation. First, the most relevant studies on this topic are described, then the mechanisms that might be accountable for this glycemic regulation impairment as exerted by hormonal contraceptives are discussed. Finally, we briefly discuss the ethical responsibility of heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 37 publications
1
17
0
2
Order By: Relevance
“…In OC user women, complications such as venous thromboembolism, stroke and coronary heart disease were frequently reported [27]. OC use is especially dangerous for women with metabolic syndrome, type-2 diabetes and hypercholesterolemia [28]. OC use also showed ambiguous correlations with cancer risk at different sites; increases the risk of overall breast cancer and cervical cancer, while significantly reduces endometrial and ovarian cancer risks.…”
Section: Discussionmentioning
confidence: 99%
“…In OC user women, complications such as venous thromboembolism, stroke and coronary heart disease were frequently reported [27]. OC use is especially dangerous for women with metabolic syndrome, type-2 diabetes and hypercholesterolemia [28]. OC use also showed ambiguous correlations with cancer risk at different sites; increases the risk of overall breast cancer and cervical cancer, while significantly reduces endometrial and ovarian cancer risks.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the reduction in insulin receptor binding occurs in the luteal phase of the menstrual cycle implicates the hormone progesterone as a modulating factor in insulin receptor binding in adipose tissue. The reduction in insulin sensitivity is also attributed to raised progesterone as seen with the COCP (Berenson, Berg, Williams, & Rahman, 2011; Cortés & Alfaro, 2014). The present study corroborates with it.…”
Section: Discussionmentioning
confidence: 99%
“…NMA evidence showed that BMI was not improved by any intervention, whereas total cholesterol levels increased with the use of OCP or pioglitazone compared with placebo and HDL levels increased with the use of spironolactone. Previous systematic reviews with meta-analysis of observational studies have shown that OCPs cause increases in total cholesterol, HDL, and triglyceride level among women with PCOS syndrome [ 45 , 47 ]. The clinical implications of the increased lipids level on cardiovascular events need long-term studies.…”
Section: Discussionmentioning
confidence: 99%